MEKANISME PENDISTRIBUSIAN KERUGIAN DALAM PERKARA CLASS ACTION DI INDONESIA - Zalfa Hania Alya; Heri Hartanto (Sebelas Maret University, 2026)
This article analyzes the mechanism for distributing damages to class members in class action lawsuits in Indonesia, focusing on Court Decisions Number 5/Pdt.G/2023/PN Sbh and Number 26/PDT.G/2009/PN.TPI. The study employs a normative juridical method with a statutory approach and a case approach to both court decisions. The research sources consist of primary and secondary legal materials. Legal materials were collected through the library research method. The analysis was conducted using a descriptive method to provide a detailed overview of the class action mechanism. The findings reveal significant variations in the implementation of damage distribution mechanisms as regulated in Article 9 of Supreme Court Regulation Number 1 of 2002. The Sibuhuan District Court applied a simple distribution system through community leaders, while the Tanjung Pinang District Court adopted a more structured mechanism by establishing a special commission. The Tanjung Pinang District Court also implemented membership verification and a clear time limit in the damage distribution process. The findings indicate that the absence of clear and consistent procedural standards in compensation distribution may impede the achievement of substantive justice for class members. The research recommends regulatory improvements to establish more systematic and measurable compensation distribution mechanisms in class action cases in Indonesia.